Pass it on : an Insiders novel - Minter, J. (New York : Bloomsbury, 2004)
Rumors are spreading about Jonathan and his friends when his dad loses all his money, Arno's parents split up, and the girls begin to act crazy.
Sequel to: The insiders.
Kliatt.
School Library Journal.
Voice of Youth Advocates (V.O.Y.A.).
Young Adult
Keywords: Dating (Social customs) -- Juvenile fiction; Families -- Juvenile fiction; Friendship -- Juvenile fiction; Dating (Social customs) -- Fiction; Family life -- Fiction; Friendship -- Fiction; Dating (Social customs) -- Fiction; Family life -- Fiction; Friendship -- Fiction; New York (N.Y.) -- Juvenile fiction; New York (N.Y.) -- Fiction; New York (N.Y.) -- Fiction